Educational Change in a Protracted Refugee Context - van der Stouwe, Marc; Oh, Su-Ann (Forced migration review, 2008)
The provision of education in the refugee camps along the Thai-Burmese border has evolved over 20 years, adapting its purpose, expanding its reach and improving its quality and relevance. Adapted from the source document.